1990
DOI: 10.1104/pp.93.3.1063
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Kinetics of the Tonoplast H+-Translocating Inorganic Pyrophosphatase and Its Activation by Free Mg2+

Abstract: To clarify the kinetic characteristics and ionic requirements of the tonoplast H+-translocating inorganic pyrophosphatase (H+-PPiase), PPi hydrolysis and PPi-dependent H+ transport were studied in tonoplast vesicles isolated from leaf mesophyll tissue of Kalanchoe Solute accumulation in plant vacuoles appears to be energized by two distinct H+-translocating enzymes at the tonoplast, an H+-ATPase and an H+-PPiases (11, 25). The tonoplast H+-ATPase has been studied extensively, and its kinetic characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 24 publications
(100 reference statements)
2
34
1
Order By: Relevance
“…The activity of the H+-PPiase is also K+ dependent and is competitively inhibited by Na+ (White et al, 1990;Rea and Poole, 1993). This suggests that the H+-ATPase will play the principal role in energizing Na+/H+ antiport activity in cells accumulating significant quantities of NaCl.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the H+-PPiase is also K+ dependent and is competitively inhibited by Na+ (White et al, 1990;Rea and Poole, 1993). This suggests that the H+-ATPase will play the principal role in energizing Na+/H+ antiport activity in cells accumulating significant quantities of NaCl.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the fact that the actual substrate of tonoplast PPase is not simply PPi, and that the free PPi is a competitive inhibitor of the tonoplast PPase (Walker and Leigh, 1981;Wang et al, 1986 ;Maeshima and Yoshida, 1989). The actual substrate of the tonoplast PPase is said to be magnesium pyrophosphate (MgPP 1 ) (Wang et al, 1986;White et al, 1990), both MgPP 1 and dimagnesium pyrophosphate (Mg 2 PP 1 ) (Walker and Leigh, 1981), or Mg 2 PP 1 alone . In contrast, the tonoplast ATPase of pineapple, K pinnata and K daigremontiana had 80 to 88% activity remaining when 3 mM MgSO 4 was replaced by 3 mM MnS0 4 and the tonoplast PPase activity of the three CAM species strictly depended on the Mg 2 + (data not shown) .…”
Section: A Tpase and Ppase Activitiesmentioning
confidence: 99%
“…However, our experimental conditions were not optimized to observe signals from the phosphates of ATP. The significance of changes in cytosolic Mg2+ may be of interest, because certain experiments have suggested that free Mg2+ is a positive allosteric modulator of the H+-PPase (White et al, 1990). It seems apparent that further investigations are necessary to understand the factor(s)…”
Section: Scussl Onmentioning
confidence: 99%